Proses Kolaborasi dalam Program Desa Binaan Imigrasi Analisis Collaborative Governance di desa Citeko Purwakarta: An Analysis of Collaborative Governance in Citeko Village, Purwakarta - Dinda Putri Nuranisya Dinda; Indra Aditya; Nidaul Muthmainnah (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2026)
The problem of non-procedural Indonesian migrant workers (PMI) in rural areas due to a lack of immigration literacy increases their vulnerability to human trafficking. Responding to this governance challenge, the Directorate General of Immigration launched the Immigration Assisted Village (DBI) Program as a collaborative preventive measure. This study aims to analyze the collaborative governance process in the implementation of the DBI program in Citeko Village, Purwakarta Regency, using the Ansell and Gash (2007) framework, which focuses on five main dimensions: face-to-face dialogue, building trust, commitment to the process, shared understanding, and intermediate outcomes. This study employed a qualitative descriptive approach. Data were collected through non-participant observation, document analysis, and in-depth interviews with six informants representing immigration authorities, village officials, and community members. The data analysis technique used the interactive model of Miles, Huberman, and Saldaña (2014). The findings indicate that all five elements of the collaborative process have been consistently implemented throughout the program's implementation. Intensive face-to-face interactions have successfully built trust among stakeholders; institutional commitment is realized through formal and informal coordination; and and fostered a strong shared understanding of the essence of preventing unsafe migration. This synchronized process has produced measurable intermediate impacts, particularly in improving residents' immigration literacy and strengthening the role of village governments in immigration oversight activities. However, the overall effectiveness of this program remains limited due to minimal private sector participation and uneven information dissemination to the grassroots level. This study contributes to the growing literature on collaborative governance of rural immigration, while also highlighting the importance of metagovernance and sustained local engagement.